THE EFFECTIVENESS OF ACTIVE LEARNING IN IMPROVING STUDENT ACHIEVEMENT IN ISLAMIC EDUCATION INSTITUTIONS - Supriadi, Eddi; Syukron, Ahmad; Masnan, Abdul Halim (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Purpose: This study analyzes the impact of active learning on improving student achievement within Islamic education. Method: Using quantitative descriptive methodology, data were collected from 88 educators in Bekasi via questionnaires and analyzed using SPSS 16.0. Result: Findings indicate active learning has substantial positive effect (p < 0.001), explaining 54.8% variance in achievement. Conclusion: Results affirm active learning promotes student engagement and aligns with Islamic education principles of ta'lim, tarbiyah, and ta'dib. Implication: This study contributes to Islamic education pedagogy by providing first empirical evidence of its effectiveness in Bekasi's Islamic institutions. Thus, active learning is recommended as strategic method for academic performance and character development.